Zarządzanie innowacjami w organizacji - Frysiak, Aneta (My University, 2014)
Moja praca została podzielona na wstęp rozdziały i zakończenie, bibliografię. W pierwszym rozdziale mojej pracy znajdują się ogólne informacje dotyczące pojęcia „innowacji” i informacje o kulturze innowacji z opisem, dlaczego kultura organizacyjna jest tak ważna w zarządzaniu innowacjami w organizacji. W drugim rozdziale przedstawiłam sfery zarządzania innowacjami w organizacji, a w podrozdziałach je opisałam . W kolejnym rozdziale opisałam metodę diagnozowania stanu innowacyjności wg Marcina Karlika, opisaną w jego książce książce pt. "Zarządzanie innowacjami w przedsiębiorstwie". Praca zawiera opis firmy ubezpieczeniowej MetLife, w której pracuję, czym się ta firma zajmuje i jakie rozwiązania posiada dla stałych i nowych klientów. W części badawczej dokonałam własnej subiektywnej oceny stanu innowacyjności MetLife, na podstawie własnych obserwacji i doświadczeń, pracując w tej organizacji. W badaniu zastosowałam metodę diagnozującą stan innowacyjności wg Marcina Karlika i zastosowałam jego siedmiokąt. We wnioskach podkreśliłam, co MetLife, moim zdaniem, powinna zrobić, by była jeszcze bardziej innowacyjna .W zakończeniu jest podsumowanie i wnioski z mojej pracy z zarządzania innowacjami w organizacji.

My work has been divided into the introduction, chapters, conclusion and bibliography. In the first chapter of my thesis I included the general information about the concept of "innovation" and culture of innovation with detailed description why organizational culture is so important in the innovation managing in the organization. In the second chapter of my thesis I presented the spheres of innovation management in organizations which I further described in details in the subsections. In the next chapter, I described the method of diagnosing the state of innovation by Martin Karlik introduced in his book titled ‘The Innovation management in the enterprise’ The paper contains a description of the MetLife insurance company where I actually work. I delineated its main tasks and what kind of proffers does it have for regular and new customers. In the research part, I made my own subjective assessment of the level of innovation in MetLife, based on my own observations and experience gathered while working in this organization. In my study, I used the method of diagnosing the state of innovation by Martin Karlik and I employed his heptagon. In the conclusion, I emphasized what, in my opinion, MetLife should exert to be even more innovative. In this part I also included the interference of my work with innovation management in the organization.
The innovation management in the organization
Keywords: zarządzanie innowacjami; kultura organizacyjna; sfery zarządzania innowacjami; siedmiokąt wg Marcina Karlika; innovation management; organizational culture; the sphere of innovation management; MetLife- company and its products; diagnostic method the state of innovation in organizations; heptagon by Martin Karlik